Ultrasonics in clinical audiometry - P, Rama Mohan Babu (Journal of All India Institute of Speech and Hearing, 1971)
Several investigators (Wegal 1932) Wever and Lawrence (1954); Deetherage et al, (1954), Corso and Oda (1961), Haaff and Knox (1963) have reported on human auditory responses to sounds of frequencies even above 10,000 HZ and upto 100,000 HZ. Corso (1965) while studying the phenomenon of high frequency and ultrasonic hearing obtained DLS for pitch and loudness at various frequencies both by air and bone conduction. Even as evidences of cochlear function at high and ultrasonic frequencies are being obtained clinicians have started speculating about the possible uses of hearing in these frequencies as a diagnostic tool. The purpose of this article is to discuss (1) the problems involved in the production, transmission and calibration of sonic and ultrasonic sounds (2) some of the studies made on the pitch and loudness discrimination functions of cochlear at high and ultrasonic frequencies and finally (3) some of the possible uses of these frequencies in the diagnosis of auditory impairments.